Bridging the Gap between Academic Preparation and Clinical Needs: A CIPP Evaluation of the English for Nursing Program (ENP) (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: To examine whether the English for Nursing Program (ENP) at STIKes Banyuwangi really supports students’ clinical communication needs and is consistent with the institution’s vision to prepare nurses who can compete internationally. Methods: A mixed-method approach was used by applying the CIPP (Context, Input, Process, Product) evaluation model developed by Daniel L. Stufflebeam. Data were collected from 32 nursing students, 2 ENP lecturers, the Head of the Nursing Study Program, 3 alumni, and 2 clinical instructors through questionnaires, interviews, document analysis, and classroom observation, then analyzed using descriptive statistics and thematic analysis. Results: The ENP goals are in line with institutional aims and national nursing standards, but the support in practice is still limited because English is only offered as a 2-credit subject in one semester. Most students rate their general English as intermediate, with listening and speaking as their weakest skills, and alumni describe their post‑ENP English as only enough for simple tasks, not for sudden or complex clinical interactions. The syllabus already includes basic nursing terms and simple nurse–patient conversations, and most students achieve good scores in conversation and presentation. However, there is still not enough time and exposure to practice more complex and authentic tasks, such as handovers or emergency scenarios. Novelty: This research applies the CIPP model in an ESP context to link ENP evaluation with real communication demands in clinical settings, not only exam scores, and offers practical suggestions such as increasing contact hours, adding realistic simulations and varied listening input, and enhancing cooperation between English lecturers and clinical instructors